Anemia in Children Co-infected with S. mansoni and Intestinal Protozoans in the Western Region (Tonkpi) of Côte d`Ivoire - Ehouman , Mocket Adolphe; Ngoran , Kouakou Eliezer; Assare , Rufin Kouassi; Ehouman , Ahossan Andre; Dosso , Pamela Nassinata; Konan , Cyrille Koffi (Recent Updates in Disease and Health Research Vol. 2, 2024)
Background: Anaemia is a serious public health problem affecting nearly 42% of children less than 5 years of age globally. In Cote d`Ivoire, 72% of the children aged 6-59 months were anemic in 2019. Anemia is defined as a reduction in the hemoglobin level in the peripheral blood below the normal threshold set for a particular population. Very commonly in the subtropics, helminthes, protozoans or malaria co-infect the same person, causing morbidities that vary according to age and region. According to the WHO, the prevalence of intestinal protozooses is high worldwide, with over 3 billion people infected, including 450 million in developing countries. This research study aims to characterize the type of anemia observed in 6 years old children infected with helminthes and protozoans in the Western part of Côte d`Ivoire, in order to improve the recommended strategy of care. Methods: The study was carried out from March 2020 to May 2021 in 22 villages of Biankouma and Man, in the Tonkpi Region, with a cohort of 451 children, both male and female, aged from 3 months to 6 years. All the children were diagnosed with anemia and collected both stool and urine for diagnosis of intestinal schistosomiasis and protozoosis. The children provided venous blood samples for the diagnosis and characterization of anemia (full blood count), and urines and stool samples were used for the diagnosis of helminthiasis and protozoosis. Univariate analysis (Chi-2 test (\(X^2\)) and P: (Probability) were used for comparison between groups. A significant test was considered at a threshold of 0.05. Results: Of the 451 children who completed the study, 221 (49.0%) were female and 230 (51.0%) were male. Helminthes infections (230, 51.0%) were more prevalent than the protozoans’ infections (40, 8.9%). 50.0% of children infected by intestinal helminthes (S. mansoni) were anemics (33.9% mild, 64.4% moderate and 1.7% severe). The characterization of anemia revealed that hypochromic microcytic anemia (HMA) was the predominant type, being found in 87 (74.8%) children. It was followed by normochromic microcytic anemia (12 children, 10.4%), normochromic normocytic anemia (09 children, 7.8%), and, finally, hypochromic normocytic anemia (08 children, 7.0%). Conclusion: S. mansoni infection was highly prevalent among 6 years old children in both sexes and in different age groups, although the number of helminthes parasites present during infections was greatest in older children. Similarly, the prevalence of anemia was high, with moderate anemia and HMA being more prevalent in 6 years old children in the western region of Côte d’Ivoire.